Difficulties Faced by 10th Grade Students in the Study of Physics. Alternatives to Improve Learning - Carranza, Carlos Francisco (2011)
This paper discusses leaming physics problems among 10th grade students of High School Education in Costa Rica. A qualitative research was conducted out of 11th grade students interviews on two different highs chools institutions of the country, Student's bad performance is not necessarily related to their level of logic and mathematical development but on some other issues such as the following. It seems not natural to start physics by teaching vectors when forces and energy are much more natural concepts to a teenager. Such a change is recommended. It is also recommended a limited use of mathematical tools, at least on initial steps, a reduction on the number of topics on the curriculum and a wide use of significative leaming strategies, instead of blackboard and chalk most used. Among such strategies daily problem-solving using the scientific method, guiding the student and let him discover natural laws by himself, using a historical approach when scientific knowledge is provided, and some other tips are suggested.